Fatores físicos e agentes químicos envolvidos na Gênese de Solos com caráter coeso - Vieira, Juliana Matos (2019)
The genesis of horizons with cohesive character is still very questioned, but it is known that their nature is pedogenetic, and may be associated with different processes of physical and chemical order. Thus, the objective of the present work was to identify and relate the physical factors and chemical agents that may be active in the genesis of horizons with cohesive character in soils of the Coastal Trays of Northeast Brazil. In chapter I, an evaluation of the physical changes in cohesive soils submitted to wetting and drying cycles through micromorphological and micromorphometric analysis and soil resistance to penetration tests. It was also evaluated the influence of the degree of selection of the sand fraction in the densification of these horizons by means of a fractionation of this fraction to evaluate the granulometric distribution of the sands in the horizons with cohesive character. In Chapter II, the contribution of low-crystallinity Si and Al compounds was investigated in the genesis of these horizons. Physical analyzes were carried out in soils with a cohesive character in the presence and absence of these compounds. The data obtained in Chapter I show that the genesis of cohesive horizons is related to a particle “packing” mechanism, facilitated by the low degree of sand selection in cohesive horizons. This mechanism occurs naturally with soil wetting and drying cycles, which, as they are increased, provide a significant reduction in soil porosity. With this reduction in porosity, the soil is more subject to chemical “cementation” and clogging of the pores with clay. The increase in the amount of wetting and drying cycles also favored the process of translocation and deletion of clay in some soils, thus suggesting that the iluvial clay is related to the genesis of cohesive soils. In Chapter II, the additions of low crystallinity silicon and aluminum to the cohesive horizons show that these compounds contribute together in the genesis of these horizons, where silica seems to have a greater cementing action than aluminum. The samples that underwent the extraction process of silica and aluminum of low crystallinity showed a significant physical improvement of the soil, verified by physical and image analysis. Thus, the contribution of these compounds in the hardening of cohesive soils is ratified. The data from the present study reinforce that the cohesive horizon genesis is multicausal and that the influence of physical factors and chemical agents in the cohesion process occur together.